Os/as trabalhadores/as do Sistema Único de Assistência Social: um enfoque às terapeutas ocupacionais - Theodoro, Andréia Martini (2024)
Since 2005, the Unified Social Assistance System (SUAS) has managed social assistance services, programs, and actions in a decentralized and participatory manner. Among the various professional categories, occupational therapy has had a historical presence in social assistance services; however, its formal recognition is recent, considering Resolution No. 17 of 2011 by the National Social Assistance Council. Thus, this study aimed to identify the professionals working within SUAS, specifically highlighting the characteristics of the professional inclusion and work of occupational therapists in different units. To achieve this, an exploratory, descriptive, and analytical study was conducted based on secondary data obtained from the official federal government database, the SUAS Census, covering the period from 2007 to 2022. The selected variables pertain to the following units: Social Assistance Reference Center (CRAS), Specialized Social Assistance Reference Center (CREAS), Specialized Reference Center for the Homeless Population (Centro Pop), Day Center, Community Center, and Shelter Unit. The data were collected, tabulated, and analyzed, covering: (1) professional categories comprising SUAS; (2) occupational therapists by sex, age group, unit, year, location (state and region), employment status, working hours, and function; (3) primary, secondary, and tertiary functions and activities of occupational therapists. An exploratory data analysis was conducted to synthesize values of the same nature, providing a global view of variations, which were described through tables, charts, and graphs. The results revealed that professionals without higher education represented the most prevalent category across different unit types. Additionally, professional categories not foreseen in legal documents were identified, as well as a significant presence of other professionals with higher education. Although in smaller numbers, professionals without higher education were found performing the role of higher-level technicians in all analyzed units. These findings indicate that, despite the guidelines established by the Basic Operational Standard – Human Resources/SUAS and Resolution No. 17/2011 for team composition in Social Assistance, some locations do not adhere to these recommendations. Regarding the professional inclusion of occupational therapists, a decrease in their number was observed, with lower representation in Day Centers and Centro Pop and greater representation in CRAS. Their role in essential services within social assistance units and their exercise of management functions are noteworthy. Based on these results, this study aims to contribute to the assessment of occupational therapists' participation in SUAS and to highlight professional inclusion trends to strengthen the profession, foster employment in the sector, and enhance the quality of assistance provided to Social Assistance Policy users.